Applied session: Elastography for muscle biomechanics - Nordez, A.; Gennisson, J.-L.; Guilhem, G.; Hug, F. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this applied session is to demonstrate the potential of shear wave elastography for the study of muscle biomechanics using both real-time demo and recent results, with a special focus on sport applications (stretching, fatigue, pain, damage).